Retrofitting Effect on the Dynamic Properties of Model-Arch Dam with and without Reservoir Water Using Ambient-Vibration Test Methods - Altunisik, Ahmet Can; Gunaydin, Murat; Sevim, Baris; Bayraktar, Alemdar; Adanur, Suleyman (ASCE-AMER SOC CIVIL ENGINEERS, 2016)
Continuous health monitoring and regular condition assessment is of vital importance for engineering structures in general and especially for arch dams. These structures can be exposed to many different loads such as earthquake, blast, wind, ice, and water pressure, which may cause deterioration and loss of structural integrity. Such development may have severe economic consequence and, more importantly, may present a serious risk to public safety. Therefore, the structural behavior of arch dams must be monitored at regular intervals during their service life, although the overall failure rate of these dams is around 1%. Experimental measurements by ambient vibration test methods are among the most commonly preferred inspection techniques for the evaluation of structural performance and safety. The aim of this research is to examine the retrofitting effect on the dynamic properties of a damaged arch dam model, with and without reservoir water, after retrofitting with high-strength structural repair mortar and carbon fiber reinforced polymer composite material. To this end, an arch dam-reservoir-foundation model was built. In the study, ambient vibration tests were carried out for three test-cases to determine changes in dynamic properties, such as natural frequency, mode shape, and damping ratio before and after retrofitting. The three cases were (1)a severely damaged dam with full reservoir (Case-A), (2)a repaired dam with full reservoir (Case-B), and (3)a strengthened dam with full reservoir (Case-C). In addition, all the measurement tests were repeated with an empty reservoir to extract the effect of water. Data for the ambient vibration tests were gathered from the dam body during vibrations by natural excitations. These excitations were provided through small impacts, and the response signals were measured by sensitivity accelerometers placed at the crest points. To obtain the experimental dynamic properties, the enhanced frequency domain decomposition method in the frequency domain was used. Comparisons of experimentally identified dynamic properties for the damaged and the retrofitted dam showed that the retrofitting application affected the structural behavior of the arch dam considerably. It was very effective in restoring the structure's original dynamic properties.
Keywords: Ambient vibration test; Arch dam-reservoir-foundation model; Carbon fiber reinforced polymer; Dynamic properties; Retrofitting; Structural health monitoring; SEISMIC RESPONSE; IDENTIFICATION; BEHAVIOR; Construction & Building Technology; Engineering